Independence Of the Country - An Example of Nationalism (Zien Journal of Social Sciences and Humanities, 2021)
The article is dedicated to the Uzbek people, its heroic struggle for independence, independence, the unique values of our ancestors, the struggle of selfless Uzbek boys in the spirit of nationalism and national and spiritual development.